Black sheep, dark horses, and colorful dogs: a review on the current state of the Gene Ontology with respect to iron homeostasis in Arabidopsis thaliana - Mai, Hans-Jörg; Baby, Dibin; Bauer, Petra (Frontiers in Plant Science, 2023)
Cellular homeostasis of the micronutrient iron is highly regulated in plants and responsive to nutrion, stress and developmental signals. Genes for iron management encode metal and other transporters, enzymes synthesizing chelators and reducing substances, transcripon factors and several types of regulators. In transcriptome or proteome datasets, such iron homeostasis-related genes are frequently found to be differenally regulated. A common method to detect whether a specific cellular pathway is affected in the transcriptome data set is to perform Gene Ontology (GO) enrichment analysis. Hence, the GO database is a widely used resource for annotang genes and idenfying enriched biological pathways in Arabidopsis thaliana. However, iron homeostasis-related GO terms do not consistently reflect gene associaons and levels of evidence in iron homeostasis. Some genes of the exisng iron homeostasis GO terms lack direct evidence of involvement in iron homeostasis. In other aspects, the exisng GO terms of iron homeostasis are incomplete and do not reflect the known biological funcons associated with iron homeostasis. This can lead to potenal errors in automac annotaon and interpretaon of GO term enrichment analyses. We suggest that applicable evidence codes should be used to add missing genes and their respecve ortholog/paralog groups to make the iron homeostasisrelated GO terms more complete, and reliable. There is high likelihood of finding new iron homeostasisrelevant members in gene groups and families like the ZIP, ZIF, ZIFL, MTP, OPT, MATE, ABCG, PDR, HMA, and HMP. Hence, we compiled comprehensive lists of genes involved in iron homeostasis that can be used for custom enrichment analysis in transcriptomic or proteomic studies, including genes with direct experimental evidence, those regulated by central transcripon factors, and missing members of small gene families or ortholog/paralog groups. As we provide gene annotaon and literature alongside, the gene lists can serve in mulple computaonal approaches. In summary, these gene lists provide a valuable resource for researchers studying iron homeostasis in A. thaliana, while they also emphasize the importance of improving the accuracy and comprehensiveness of the Gene Ontology.